Cloud computing and services science : 6th International Conference, CLOSER 2016, Rome, Italy, April 23-25, 2016, Revised selected papers /: 6th International Conference, CLOSER 2016, Rome, Italy, April 23-25, 2016, Revised selected papers. (2017) - Unknown
No abstract available